AXIOMATIZING SEMANTIC THEORIES OF TRUTH?. Issue 2 (26th January 2015) - FISCHER, MARTIN; HALBACH, VOLKER; KRIENER, JÖNNE; STERN, JOHANNES
Abstract: We discuss the interplay between the axiomatic and the semantic approach to truth. Often, semantic constructions have guided the development of axiomatic theories and certain axiomatic theories have been claimed to capture a semantic construction. We ask under which conditions an axiomatic theory captures a semantic construction. After discussing some potential criteria, we focus on the criterion of ℕ-categoricity and discuss its usefulness and limits.